What Do CDC’s Surveys Say About the Prevalence of Defensive Gun Use? - Kleck, Gary (American journal of criminal justice, 2021)
In 1996, 1997, and 1998, the Centers for Disease Control and Prevention (CDC) conducted large-scale surveys asking about defensive gun use (DGU) in four to seven states. Analysis of the raw data allows the estimation of the prevalence of DGU for those areas. Data pertaining to the same sets of states from the 1993 National Self-Defense Survey (Kleck & Gertz, 1995 ) allow these results to be extrapolated to the U.S. as a whole. Possible sources of error in surveys of DGU are reviewed, and the results of previous surveys compared. CDC’s survey data confirm previous high estimates of DGU prevalence, disconfirm very low estimates derived from the National Crime Victimization Survey, and indicate that defensive uses of guns by crime victims are far more common than offensive uses by criminal offenders.